2008
DOI: 10.1016/j.phytochem.2007.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Furoquinoline alkaloids of Ertela (Monnieria) trifolia (L.) Kuntze from the Suriname rainforest

Abstract: 7-(2'-Hydroxy-3'-chloroprenyloxy)-4,8-dimethoxyfuroquinoline (1) and 6-(2'-hydroxy-3'-chloroprenyloxy)-4,7-dimethoxyfuroquinoline (2), together with ten known compounds, have been isolated from the aerial parts of Ertela (Monnieria) trifolia (L.) Kuntze. All the isolates were tested for antiproliferative activity against the A2780 human ovarian cancer cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…In addition to anticancer activity, the intermediates of furoquinoline synthesis and furoquinoline derivatives have been revealed to exhibit diverse pharmacological effects, such as 5-HT2 receptor antagonist activity (24), vasorelaxation via the suppression of calcium influx (25), anti-allergic effects (9) and the blocking of outward K + current and Na + channels (5). A previous study revealed that the intermediates of furoquinoline synthesis exhibited moderate inhibitory effects on the growth of human ovarian cancer A2780 cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to anticancer activity, the intermediates of furoquinoline synthesis and furoquinoline derivatives have been revealed to exhibit diverse pharmacological effects, such as 5-HT2 receptor antagonist activity (24), vasorelaxation via the suppression of calcium influx (25), anti-allergic effects (9) and the blocking of outward K + current and Na + channels (5). A previous study revealed that the intermediates of furoquinoline synthesis exhibited moderate inhibitory effects on the growth of human ovarian cancer A2780 cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…The second challenge was equipping BGVS to make the extracts from a variety of plant samples, and the third challenge was isolating novel natural products from extracts that were identified only by a code number. The last challenge made the natural products work more difficult, but it was eventually overcome, and a variety of novel bioactive natural products were isolated and identified, including diterpenoids, , alkaloids, and saponins. The most interesting and potent compounds found were the ipomoeassins A–F ( 47 – 52 ) from Ipomoea squamosa . , These compounds, and especially ipomoeassins D ( 50 ) and F ( 52 ), had antiproliferative activities in the 35 nM range against the A2780 ovarian cancer cell line. Their unique structures and potent activities generated successful syntheses by Fürstner, , Postema, and Shi, and the Shi group has gone on to carry out structure–activity relationship and mechanism of action studies, which revealed that ipomoeassin F inhibits protein translocation by binding to Sec61α (protein transport protein Sec61 subunit alpha isoform 1).…”
Section: International Cooperative Drug Discoverymentioning
confidence: 99%
“…Pierre (Sapotaceae) and Genipa americana L. (Rubiaceae) collected at Asindopo village, Suriname, yielded the known cryptolepine hydrochloride (Yang et al, 1999a). From the aerial parts of Monnieria trifolia L. (Rutaceae) from Suriname, ten alkaloids were purified (Cao et al, 2008). Bioassay-guided fractionation of the alkaloid portion of a CH 2 Cl 2 -MeOH extract of Tabernaemontana calcarea Pichon (Apocynaceae) from Madagascar resulted in the isolation of fifteen alkaloids (Chaturvedula et al, 2003b).…”
Section: Bioactive Compounds Of Higher Plants From Suriname and Madagmentioning
confidence: 99%